Daya Tarik Halal Tourism Pada Minat Wisatawan di Indonesia Ketika Era Covid-19 - Aula Nurul Ma’rifah; Khavid Normasyhuri (ITB AAS INDONESIA Surakarta, 2022)
The Covid-19 pandemic has become a global pandemic and affects various sectors including tourism. The tourism sector was greatly affected because various destinations and tourism supporting products had to be closed to reduce the spread of Covid-19. However, recently various tourism destinations and products have begun to be opened by continuing through health protocols or vaccinations. Global tourism shows development and is familiar with the concept of halal tourism. The attraction of halal tourism includes not only destinations but also tourism products and services that are closely related to Islamic values. In addition, halal tourism can not only be enjoyed by Muslim tourists but also non-Muslim tourists by not violating Islamic law and providing the convenience of worshiping Muslim tourists. The research uses a quantitative approach to field research and uses a questionnaire with a Likert scale. The research was conducted in Indonesia with the aim of seeing whether the attractiveness of halal tourism is able to influence tourist interest in traveling during the Covid-19 pandemic. The results of the study show that the attractiveness of halal tourism can have a positive effect on tourist interest in traveling during the Covid-19 pandemic.